2013
DOI: 10.1007/s00167-013-2780-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of knee functional flexion axis in navigated TKA: identification and repeatability before and after implant positioning

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 47 publications
(85 reference statements)
1
22
1
Order By: Relevance
“…4,5 Several surgical techniques with functional or anatomical reference axes have been developed and introduced to achieve this goal. 6 A successful outcome is believed to be dependent on the restoration of a neutral mechanical axis in the lower extremity, with the femoral and tibial components aligned perpendicular to the mechanical axis in the coronal plane. Although mechanical alignment (MA) is the most common surgical technique in TKA for restoring patient function, 15 to 25% of the patients have reported dissatisfaction, and 10% required revision surgery within 10 years of the surgery.…”
mentioning
confidence: 99%
“…4,5 Several surgical techniques with functional or anatomical reference axes have been developed and introduced to achieve this goal. 6 A successful outcome is believed to be dependent on the restoration of a neutral mechanical axis in the lower extremity, with the femoral and tibial components aligned perpendicular to the mechanical axis in the coronal plane. Although mechanical alignment (MA) is the most common surgical technique in TKA for restoring patient function, 15 to 25% of the patients have reported dissatisfaction, and 10% required revision surgery within 10 years of the surgery.…”
mentioning
confidence: 99%
“…Limitations. Firstly, previous studies have confirmed that the rotation axis fluctuates dynamically around sTEA during the knee movement [29]. In this study, a single sTEA was HKA: hip-knee-ankle angle; PFA: patella transverse axis-femoral transepicondylar axis angle; HSS: Hospital for Special Surgery, KSS Knee Society Score; "−" indicates that the angle opens inwards.…”
Section: Satisfactory Clinical Efficacymentioning
confidence: 54%
“…Firstly, previous studies have confirmed that the rotation axis fluctuates dynamically around sTEA during the knee movement [ 29 ]. In this study, a single sTEA was used as the reference standard, which might lead to inaccuracy in partial angle range.…”
Section: Discussionmentioning
confidence: 86%
“…8 In this work, the flexion axes were found to lie in a similar anatomical location to previous reports. 15,20,41,42 The FFA lay posterior and inferior with respect to the TEA. An interesting observation was that the implanted knee maintained an axis in proximity to the FFA (posterior and inferior to the TEA).…”
Section: Discussionmentioning
confidence: 94%
“…This has highlighted the potential clinical relevance of FFA. Colle et al 41 performed kinematic analysis on 87 patients undergoing TKA and analysed angle differences between the FFA and the TEA pre- and post-TKA in the frontal and axial planes. They noted that the most significant differences between the two were seen in the frontal plane and assigned such difference to condylar wear from osteoarthrosis.…”
Section: Discussionmentioning
confidence: 99%